The Compilation of a Greek Environmental input-output table for 2005 - Economidis, Charalambos; Keramidas, Dimitrios; Demertzi, Aggeliki; Stromplos, Nikos; Sfetsos, Athanasios (SPOUDAI Journal of Economics and Business, 2009)
This paper discusses the compilation of an Environmental Input-Output Table for Gre ece for the year 2005. The objective of this work is to discover the relationships and interdependencies between activities disaggregated in economic branches on a country level and air emissions through a series of indicators. The relationship between economic activity and the environment is determined through a set of indicators that include direct and indirect emission intensity coefficients and the effect of emission factor intensity on the components of final demand. The basic data on air emissions were prepared by the Greek Ministry of the Environment and Public Works. The economic data are from the 2005 Input-Output Table for the Greek Economy produced by the National Statistical Service of Greece. JEL Classifications: D570, Q500